Macroeconomic Determinants of International Migration to the UK - Giuseppe Forte; Jonathan Portes (Global Labor Organization (GLO), 2017)
This paper examines the determinants of long-term international migration to the UK; we explore the extent to which migration is driven by macroeconomic variables (GDP per capita, unemployment rate) as well as law and policy (the existence of “free movement” rights for EEA nationals). We find a very large impact from free movement within the EEA. We also find that macroeconomic variables – UK GDP growth and GDP at origin – are significant drivers of migration flows; evidence for the impact of the unemployment rate in countries of origin, or of the exchange rate, however, is weak. We conclude that, while future migration flows will be driven by a number of factors, macroeconomic and otherwise, Brexit and the end of free movement will result in a large fall in immigration from EEA countries to the UK.
Keywords: F22; J61; J68; 330; Brexit; EU; Immigration; UK